Design and fabrication of high power InGaN blue laser diode over 8 W. (July 2021) - Zhong, Zhibai; Lu, Shiqiang; Li, Jinchai; Lin, Wei; Huang, Kai; Li, Shuping; Cai, Duanjun; Kang, Junyong
Highlights: The impact of MQWs on the performance of the InGaN blue LD was numerically investigated. The facet coating effect on the COD level was studied. The LD coated with the Al2 O3 and Al2 O3 /Ta2 O5 films by ECR deposition had the highest COD level. The output power of the blue LDs as high as 8.04 W was achieved at 5.5 A. Abstract: The impact of multi quantum wells (MQWs) structure on the homogeneity of spontaneous luminescence and quantum efficiency of the high power InGaN blue laser diode (LD) is numerically investigated. The structure with 2QWs in the active region is found to be the optimal choice for the high power InGaN LD. Accordingly, the edge emitting LD structure is grown and fabricated. To study the facet coating effect on the catastrophic optical damage (COD) level, three types of LDs are coated with different materials by different techniques, respectively. The characterization results confirm that the single blue LD coated with the Al2 O3 and Al2 O3 /Ta2 O5 films by electron cyclotron resonance deposition exhibits the highest COD level, due to the better crystal quality and interfacial quality of the coated films. The LD starts to operate at 1.04 kA/cm 2 with slope efficiency of 1.8 W/A and the wavelength of 444.9 nm. As a result, the output power as high as 8.04 W is achieved at 5.5 A.